Effect of the heart of date palm aqueous extract administration on antioxidant enzymes and obesity-related hormones levels in rats - Trabzuni, Dina Mohammed (Progress in Nutrition, 2019)
The aim of this study was to determine the levels of antioxidant enzymes and some hormones in rats samples after administration of aqueous extracts of heart of date palm (HDP). HDP extracts were prepared from three Saudi date palm cultivars (Sukkari, Naboat Saif and Solleg) and administered orally every day for eight weeks. Activities of glutathione peroxidase (GPx) superoxide dismutase (SOD) and Catalase (CAT) were determined in rat liver and plasma, while Leptin, Ghrelin, Insulin and glucose were determined only in plasma. Animals in all groups had normal growth and health through the experiment. The results showed significant increase in activities of GPx, SOD and CAT in both rat liver and plasma. Circulating levels of leptin and insulin decreased significantly after administration of the three HDP extracts to the animals. Only the level of ghrelin in rat plasma increased significantly (p< 0.05) in case of Sukkari HDP extract. Although HDP have significant effects on leptin, ghrelin and insulin in rats, relationship of HDP administration to obesity could not be confirmed, and further research is needed to investigate the effect of HDP on human body weight control.